Lived things : materialities of agency, affect, and meaning in the short fiction of Djuna Barnes and Jean Rhys - Oulanne, Laura, 1985- (Helsinki : University of Helsinki, 2018)
Tiivistelmä.
Väitöskirja
Julkaistu myös painettuna.
Keywords: Barnes, Djuna; Rhys, Jean; 1900-luku.; 1900-talet.; kirjallisuudentutkimus; materiaalisuus; novellit; litteraturvetenskap; materialitet; noveller; väitöskirjat; doktorsavhandlingar